Chromosome-level genome assembly and annotation of the White-spotted spinefoot Siganus canaliculatus - Xiaolin Huang; Yanke Lu; Hui Zhang; Lin Xian; Shiting Huang; Yukai Yang; Lei Wang; Dianchang Zhang; Chao Li (Scientific Data)
Abstract The White-spotted spinefoot S. canaliculatus, is an economically important marine fish in South China and featured by possessing poisonous glands in its fin spines. However, the unavailability of the S. canaliculatus genome has been a serious obstacle to genetic breeding as well as basic researches such as uncovering genomic basis underlying its toxigenic glands. Here, we presented a chromosome-level genome assembly coupled with good annotation of S. canaliculatus using multiple omics technologies. The assembled genome size was 547.39 Mb, with a contig N50 and scaffold N50 length of 21.41 Mb and 21.79 Mb, respectively. Approximately 95.32% (521.76 Mb) of assembled sequences were placed into 24 pseudochromosomes with the support of Hi-C contact map. Furthermore, around 16.37% of the genome was composed of repetitive elements. The quality of the assembly assessed using BUSCO showed that 98.6% of BUSCO genes were identified as complete. 25,323 protein-coding genes were predicted after integration of three kinds of evidence, of which 96.96% were functionally annotated in at least one of nine protein databases. In sum, the chromosome-level genome assembly and annotation provide fundamental resources for genetic breeding and molecular mechanism related studies of S. canaliculatus.